Dopaminergic Modulation of Striatal Inhibitory Transmission and Long-Term Plasticity - Elizabeth Nieto Mendoza; Elizabeth Hernández Echeagaray (Neural Plasticity)
Dopamine (DA) modulates glutamatergic synaptic transmission and its plasticity in the striatum; however it is not well known how DA modulates long-term plasticity of striatal GABAergic inhibitory synapses. This work focused on the analysis of both dopaminergic modulation of inhibitory synapses and the synaptic plasticity established between GABAergic afferents to medium spiny neurons (MSNs). Our results showed that low and high DA concentrations mainly reduced the amplitude of inhibitory synaptic response; however detailed analysis of the D1 and D2 participation in this modulation displayed a wide variability in synaptic response. Analyzing DA participation in striatal GABAergic plasticity we observed that high frequency stimulation (HFS) of GABAergic interneurons in the presence of DA at a low concentration (200 nM) favored the expression of inhibitory striatal LTD, whereas higher concentration of DA (20 μM) primarily induced LTP. Interestingly, the plasticity induced in an animal model of striatal degeneration mimicked that induced in the presence of DA at a high concentration, which was not abolished with D2 antagonist but was prevented by PKA blocker.